I started out doing this problem, and got 2 of the answers correct. However in the back of my book there is 1 more answer, and I don't understand it.
2x^4 = 16x
2x^4 - 16x = 0
2x(x^3 - 8)
x = 0, x = 2, (and the 2 answers I don't understand) x = -1 + i*sqrt(3), -1 - i*sqrt(3)
I just don't understand where the imaginary answers came from.
Thanks for your help
2x^4 = 16x
2x^4 - 16x = 0
2x(x^3 - 8)
x = 0, x = 2, (and the 2 answers I don't understand) x = -1 + i*sqrt(3), -1 - i*sqrt(3)
I just don't understand where the imaginary answers came from.
Thanks for your help